STUDENT TEACHERS’ PERCEPTIONS OF THEIR READINESS FOR THE INTERNSHIP - Maharani, Amanda Vira (SUAR BETANG, 2018)
This descriptive qualitative study aims to investigate English student teachers? perceptions of their readiness to take the internship regarding some aspects. The data were mainly collected through interviews. The interviewees were six students in the sixth semester of ELT program of the State University of Malang. The researcher recruited six student teachers with high, average, and low achievement based on their GPA. The data were analyzed descriptively according to three steps which consist of data reduction, data display, and conclusion drawing. The research showed that the student teachers were still feeling not ready enough in some aspects. The first aspect is almost all of them had an issue with the duration of the internship that is too short. Second, not all the student teachers majoring English Language Teaching have a desire to be a teacher although teaching is the primary field of work that they have been prepared for throughout their university study. Third, another factor that makes them feel unready is anxiety. Fourth, from the content courses aspect, there was an issue with the seq uences of the courses that made student teachers confused in planning a lesson. Lastly, regarding skill courses, the respondents thought the courses are already adequate, and they already got good scores, but they stated that they still have some issues with it(Persepsi Mahasiswa KPL tentang Kesiapan Mereka untuk Menjalani KPL Keguruan)Penelitian deskriptif kualitatif ini bertujuan untuk mencari tahu kesiapan mahasiswa KPL Jurusan Sastra Inggris untuk menjalani KPL Keguruan di beberapa aspek. Data penelitian ini didapatkan melalui wawancara. Subjek yang diwawancai adalah enam mahasiswa semester enam dari Pendidikan Bahasa Inggris, Universitas Negeri Malang. Peneliti merekrut enam mahasiswa KPL dengan prestasi tinggi, sedang, dan rendah berdasarkan IPK. Data penelitian dianalisis berdasarkan tiga tahapan yang terdiri atas reduksi data, penyajian data, dan penarikan simpulan. Penelitian menunjukkan bahwa mahasiswa KPL masih belum siap di beberapa aspek. Aspek pertama adalah hampir semua dari enam mahasiswa KPL memiliki pemikiran bahwa durasi dari KPL Keguruan terlalu singkat. Kedua, tidak semua mahasiswa KPL Pendidikan Bahasa Inggris memiliki minat untuk menjadi guru walaupun mengajar adalah peluang kerja yang dipersiapkan selama belajar di universitas. Ketiga, faktor lain yang membuat mereka tidak siap adalah kegelisahan. Keempat, dari aspek mata kuliah konten terdapat isu tentang urutan mata kuliah yang membuat mahasiswa KPL bingung tentang perencanaan pembelajaran. Terakhir di aspek mata kuliah kecakapakan berbahasa Inggris, responden mengatakan bahwa mata kuliah tersebut sudah cukup membantu dan nilainya sudah mencukupi, tetapi mereka masih memiliki beberapa permasalahan